2016
DOI: 10.3390/magnetochemistry2040046
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Ethylenedithio-MPTTF-PTM Radical Dyad as a Potential Neutral Radical Conductor

Abstract: During the last years there has been a high interest in the development of new purely-organic single-component conductors. Very recently, we have reported a new neutral radical conductor based on the perchlorotriphenylmethyl (PTM) radical moiety linked to a monopyrrolotetrathiafulvalene (MPTTF) unit by a π-conjugated bridge (1) that behaves as a semiconductor under high pressure. With the aim of developing a new material with improved conducting properties, we have designed and synthesized the radical dyad 2 w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Therefore, the coupling and column chromatography steps were carried out at the alcohol stage. Earlier reports aiming at building conjugated systems with perchlorinated trityl radicals (PTM-radicals) used Horner–Wadsworth–Emmons reactions, , which are less versatile then the Suzuki–Miyaura reaction employed here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the coupling and column chromatography steps were carried out at the alcohol stage. Earlier reports aiming at building conjugated systems with perchlorinated trityl radicals (PTM-radicals) used Horner–Wadsworth–Emmons reactions, , which are less versatile then the Suzuki–Miyaura reaction employed here.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier reports aiming at building conjugated systems with perchlorinated trityl radicals (PTM-radicals) used Horner− Wadsworth−Emmons reactions, 60,61 which are less versatile then the Suzuki−Miyaura reaction employed here. Sonogashira−Hagihara Coupling.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Absorption spectra of radical dyad 1 were measured in different solvents in order to compare it with the solvatochromic behavior observed in related TTF‐PTM radical dyads . This solvatochromism is assigned to the bistability phenomenon between neutral and zwitterionic species since polar solvents can induce an intramolecular electron transfer process from the electron‐donor TTF unit to the electron‐acceptor PTM radical.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular radical units with unpaired electrons have been the basis of one of the earliest devised strategies for achieving organic conductors. In the contribution of Manuel Souto et al [6], a new molecular dyad is reported, based on a monopyrrolo-tetrathiafulvalene electron donor linked by a π-conjugated bridge to a perchlorotriphenylmethyl radical, with interesting properties and the potential to give rise to new radical conductors in the solid state. The combination of radical units with electroactive donor networks is another strategy for preparing magnetic conductors, and in this issue Kazuki Horikiri and Hideki Fujiwara describe charge transfer salts of a new EDT-TTF (ethylenedithiotetrathiafulvalene) donor containing a radical through a π-conjugated vinylene spacer, with diamagnetic GaCl 4 and paramagnetic FeCl 4 anions with strong π-d interactions [7].…”
mentioning
confidence: 99%